Our changing family : a study on family beliefs and practices - Peh, Rebecca Min-Li (2016)
This research aims to show that individuals are human actors who have agency in shaping their family lives through the various strategies they adopt vis-à-vis social structures. Specifically, the research examines the ideas and experiences that individuals have concerning the upbringing of children, gendered family arrangements and work-life balance. Using the theoretical framework of agency and structure, the study seeks to address the scarcity of qualitative research on the contemporary Singaporean family. Through in-depth interviews with middle-aged respondents in Singapore, the findings demonstrate how individuals hold the capacity to act and react to the changing social environment amidst the expectations thrust upon them. Instead of a total compliance to state ideals and social structures, the respondents expressed how they negotiate the demands of work and family. Exposed to both traditional and modern cultural imperatives, middle-aged individuals adapt to their contemporary surroundings by amalgamating both the old and the new in the creation of nuanced family strategies and beliefs. Thus the family is a site brimming with subjective experiences and meanings that arise through the interplay between individual autonomy and structural conditions.